Sensitivitas Interkultural Antarumat Beragama di Kota Palembang - Adi Inggit Handoko; Rindang Senja Andarini; Febrimarani Malinda (Jurnal ILMU KOMUNIKASI, 2022)
Religious differences often trigger conflict in a multicultural society. Palembang, with its diverse community characteristics, is claimed as zero conflict area. This study aims to see intercultural sensitivity among religious people in Palembang. This qualitative research uses a case study approach with the theory of the Developmental Model of Intercultural Sensitivity. Data were collected through in-depth interviews with religious leaders. The results shows that each religious group tries to emphasize ethnorelativism through tolerance, mutual cooperation in building houses of worship, friendship relations with different adherents. However, at some levels, ethnic prejudices and stereotypes against different religious people still emerge.